2014
DOI: 10.3109/13814788.2014.899349
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate prescribing according to the STOPP/START criteria in older people from a primary care setting

Abstract: According to STOPP/START criteria, there is a high level of PIM in PHC setting. To prevent PIM occurring, action must be taken.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
24
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 29 publications
8
24
1
3
Order By: Relevance
“…Consistent with previous studies using both versions 1 and 2 of the STOPP criteria, this study identified a significant association between polypharmacy (>5 medications) and prescription of at least one PIM [25,30,32,33,[35][36][37][38][39][40][41][42][43][44][45]. The association between PPO occurrence and polypharmacy identified in this study has been less consistently reported elsewhere [33,36,37,46]. It is possible that prescribers may regard an increased medication burden and the resulting increased risk of adverse drug reactions as a barrier to the addition of further medication despite the potential for benefit, thus creating a 'treatment-risk paradox' [47].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with previous studies using both versions 1 and 2 of the STOPP criteria, this study identified a significant association between polypharmacy (>5 medications) and prescription of at least one PIM [25,30,32,33,[35][36][37][38][39][40][41][42][43][44][45]. The association between PPO occurrence and polypharmacy identified in this study has been less consistently reported elsewhere [33,36,37,46]. It is possible that prescribers may regard an increased medication burden and the resulting increased risk of adverse drug reactions as a barrier to the addition of further medication despite the potential for benefit, thus creating a 'treatment-risk paradox' [47].…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with previous studies using both versions 1 and 2 of the STOPP criteria, this study identified a significant association between polypharmacy (>5 medications) and prescription of at least one PIM . The association between PPO occurrence and polypharmacy identified in this study has been less consistently reported elsewhere .…”
Section: Discussionsupporting
confidence: 88%
“…We found that the prevalence of Beers 2012 criteria PIMs in the total cohort was 44.4 %, whereas other studies reported a prevalence of between 22.9 and 58.4 % [13,14,29,30]. We found the prevalence of STOPP & START 2008 criteria PIMs and PPOs to be, respectively, 34.1 and 57.7 %, whereas Castillo-Páramo et al [31] reported a prevalence of PIMs of 37.5 % in a primary care setting; the prevalence of PPOs was 45.9 %. This difference may have occurred because This was the first study to investigate the association between PIMs identified with the Beers 2012 or STOPP 2008 criteria and medication-related hospital admissions; however, it had several limitations.…”
Section: Discussioncontrasting
confidence: 60%
“…This problem leads to increased morbidity or mortality and treatment failure. 4 The reported prevalence of under-prescription ranges from 22.7 to 84.8%, [5][6][7][8][9][10] which depends on the population of the study and the criteria to define under-prescription. According to the START criteria that divide medication omissions by organ system, 16.5-33.4% of medications are omitted in elderly diabetic patients.…”
Section: Introductionmentioning
confidence: 99%
“…According to the START criteria that divide medication omissions by organ system, 16.5-33.4% of medications are omitted in elderly diabetic patients. 5,7,8 One study that evaluated elderly patients during hospital admission found that 64.6% of elderly diabetic patients had at least one medication omission which was significantly higher than non-diabetic patients. 11 Diabetes has many complications.…”
Section: Introductionmentioning
confidence: 99%